À propos de deux cas de brucellose dans le sud de la France aux époques médiévale et moderne (Abbaye Saint-Sauveur, Aniane ; La Closeraie, Aix-en-Provence) - Avril Meffray; Philippe Biagini; Catherine Rigeade; Michel Panuel; Laurent Schneider; Yann Ardagna (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Brucellosis, known as "Mediterranean fever", has been an endemic zoonosis in human societies, especially in rural and island environments, for thousands of years. The macroscopic characteristics of this infection by Brucella bacteria are well defined, but they are difficult to assess in palaeopathological diagnoses, as reflected by the small number of cases in the relevant literature. This is due to the rather complex differential diagnosis of the disease, in particular involving other infections with a predilection for the spine which were very frequent in past populations. This article presents the results of a study of two unpublished cases of brucellosis, one from the mediaeval Carolingian monastic complex of Saint-Sauveur d’Aniane (34), and the other from the mediaeval and modern cemetery of La Closeraie, in Aix-en-Provence (13). The aim of this article is therefore to present the palaeopathological data obtained for these subjects, in whom macroscopic lesions observed on the lumbar spine, supported by medical imaging, suggest brucellosis. These new findings demonstrate the need to broaden the scope of approaches in order to reinvestigate this pathology in ancient contexts. Our aim is to invite anthropological biologists to consider this diagnostic possibility in their studies of osteoarchaeological series, whether newly discovered or already uncovered in the past.